PERAN BADAN PERENCANAAN PEMBANGUNAN DAERAH DALAM PENYUSUNAN RPJMD KOTA TOMOHON - LANTAEDA, SYARON BRIGETTE; LENGKONG, FLORENCE DAICY; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Development is a process of continuous improvement of a society or a social system as a whole towards a betterlife. The government is the most important party and acts as a driver in development, namely through development planning.Development planning is a government effort to coordinate all economic decisions in the long run to directly influence andcontrol the growth of important economic variables. In Law no. 25 Year 2004 About National Development PlanningSystem, Development Planning Agency at Sub-National Levelhas an important role in implementing regional planning. Local development planning planned by Bappeda starts from thevillage / sub-district, sub-district, district and city level, to the provincial level through (Development Planning Meeting). Inthe planning of this regional development required the participation of local communities in the implementation ofdevelopment in the region. The role of Regional Development Planning Board is very complex in the implementation ofregional development planning, meaning that all areas of development planning are handled under the RegionalDevelopment Planning Board, as well as regional economic development planning. This study aims to find out how the roleof the Regional Development Planning Agency) in Tomohon City. Data collection is done by interviewing key informants(key informants), observation and documentation. The method used in this research is descriptive that is the method usedto analyze the data by describing or describing the data that has been collected as it is. Based on the results of researchconducted shows that the Role of Development Planning Agency (Tomohon City. This can be seen from the role indicatorthat is based on the main tasks and functions of Bappeda itself, the mechanism by which Development Planning Agency atSub-National Levelin improving economic development and the problems faced in the development planning.Keywords: Role, Regional Development Planning Board, Development of Medium Term Development Plan Area